1988
DOI: 10.1084/jem.168.2.687
|View full text |Cite
|
Sign up to set email alerts
|

Normal mouse peritoneum contains a large population of Ly-1+ (CD5) B cells that recognize phosphatidyl choline. Relationship to cells that secrete hemolytic antibody specific for autologous erythrocytes.

Abstract: The most remarkable feature of the immune response is its ability to generate cells and antibodies specifically reactive with an enormous variety of foreign antigens while normally avoiding the production of autoreactive elements. An accumulating body of data demonstrates that a distinct lineage of B cells (1), the Ly-1 + B cell subset, does not display this feature, but rather is associated with the production ofautoreactive antibodies (2). We are unaware of autoimmune pathology directly demonstrated to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(129 citation statements)
references
References 38 publications
6
123
0
Order By: Relevance
“…For four-color staining, biotin-labeled anti-PD-L2 and streptavidin-APC were used. PtC-bearing, fluorochrome-encapsulating liposomes [10] were the kind gift of Dr. S. H. Clarke (University of North Carolina, Chapel Hill, NC). Data were acquired using a FACSCalibur flow cytometer (BD Biosciences) with CellQuest software (BD Biosciences) and were analyzed using FlowJo software (TreeStar).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 3 more Smart Citations
“…For four-color staining, biotin-labeled anti-PD-L2 and streptavidin-APC were used. PtC-bearing, fluorochrome-encapsulating liposomes [10] were the kind gift of Dr. S. H. Clarke (University of North Carolina, Chapel Hill, NC). Data were acquired using a FACSCalibur flow cytometer (BD Biosciences) with CellQuest software (BD Biosciences) and were analyzed using FlowJo software (TreeStar).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Reconstitution of anti-PtC IgM in sIgM-deficient mice substantially reduced the bacterial load in a cecal ligation and puncture model [5]. Thus, V H 11/V H 12-expressing B1 cells play an important role in immunity; considering that PtC-binding B1 cells recognize protease-treated autologous erythrocytes, they may play a role in hemolytic autoimmune dyscrasias as well [10,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One highly represented example is the specificity encoded by germline V H 11 and V 9 Ig genes. This rearrangement is expressed by 5-15% of the peritoneal B-1 cells in normal mice and reacts with phosphatidylcholine (PtC), a normal component of the cell membrane (24). We recently reported that B cells constrained by a V H 11V 9 Ig transgene generated CD5 ϩ , PtC-specific B cells in both the spleen and peritoneum (22).…”
mentioning
confidence: 99%